Three Years of ACB Phase Function Observations from the Mars Science Laboratory: Interannual and Diurnal Variability and Constraints on Ice Crystal Habit - Alex C. Innanen; Brittney A. Cooper; Conor W. Hayes; Charissa L. Campbell; Jacob L. Kloos; Scott D. Guzewich; John E. Moores (The Planetary Science Journal, 2024)
We examine 3 yr of phase-function observations of water-ice clouds taken during the Aphelion Cloud Belt season by the Mars Science Laboratory (MSL). We derive lower-bound single-scattering phase functions for Mars years (MYs) 34, 35, and 36, over a range of scattering angles from 45° to 155°, expanding on the MY 34 phase function previously derived from MSL observations using the same method. We also modify the procedure used for MY 34 to make use of cloud opacity values derived from other MSL observations, often taken in conjunction with the phase-function observations. From these, we see little variability, both interannually and diurnally in the phase function at Gale Crater. We use our derived phase functions to attempt to constrain a dominant ice-crystal geometry by fitting a two-term Henyey–Greenstein function. In comparing to HG functions of Martian dust and modeled water-ice crystals, we see agreement especially with droxtal water-ice crystals, dust at Gale crater, and irregular volcanic glasses. This could be indicative of crystals composed of some irregular shape.